Signs of Urban Evolution? Morpho-Functional Traits Co-variation Along a Nature-Urban Gradient in a Chagas Disease Vector - Montes de Oca-Aguilar, Ana C.; González-Martínez, Adriana; Chan-González, Raúl; Ibarra-López, Pilar; Smith-Ávila, Selene; Córdoba-Aguilar, Alex; Ibarra-Cerdeña, Carlos N. (Frontiers in Ecology and Evolution, 2022)
Environmental change (i.e., urbanization) impacts species in contrasting ways, with some species experiencing benefits given their way of life (i.e., blood-sucking insects). How these species respond to such change is not well understood and for species involved in human diseases, this “how” question is particularly important. Most Triatominae bug species inhabit tropical and subtropical forests where their vertebrate hosts’ temporal abundance depends on climate seasonality. However, in human encroached landscapes, triatomines can benefit from resource stability which may lead to adaptive phenotypic change to track novel hosts. We tested for an association between different landscapes and morpho-functional traits linked to sensory, motion, and feeding functions in Triatoma dimidiata and compared fecundity (i.e., number of eggs) in each landscape as a proxy of fitness. Using geometric and traditional morphometric tools, we predicted a morphological simplification in bugs inhabiting urbanized areas. While wing morphology or proboscis were not influenced by landscape class, the opposite occurred for thorax morphology and number of sensilla. Wing and thorax morphology did not covary under modified landscape scenarios, yet we detected a morpho-functional convergence for thorax size and antennal phenotype in both sexes, with a simplification trend, from nature to urban settings. Given no fecundity differences across landscapes, there is no potential reproductive costs. Moreover, the convergence of thorax size and antennal phenotype suggests differences in flight/locomotion performance and host/environment perception, as a possible adaptive response to relaxed selective pressures of the bug’s native habitat. These results imply that T. dimidiata could be adapting to urbanized areas.